Study on spontaneous combustion characteristics of water-soaked coal - Zhu CHEN; Mingwei XU; Haobin LI; Liang BAI; Yongliang YANG; Shangxue YANG; Yage LI (Meikuang Anquan)
In order to investigate the influence degree of water-soaked coal with different moisture contents on coal spontaneous combustion, coal samples with different moisture contents are prepared, programmed temperature experiment was used to test the thermal weight and CO production rate of coal samples, and SEM (Scanning Electron Microscope) was used to observe the surface morphology characteristics of coal samples with different moisture contents. The results show that moisture can change the thermal decomposition characteristics of coal; when the moisture content of coal is 6%-14%, the temperature required for coal spontaneous combustion decreases with the increase of moisture content, which reduces the process of coal spontaneous combustion; when the moisture content of coal is 14%-36%, the temperature required for coal spontaneous combustion increases with the increase of moisture content, which prolongs the process of coal spontaneous combustion. The study also found that moisture can affect the oxidation characteristics of coal, when the moisture content is lower than a certain value, increasing the moisture content of coal can promote the release of CO and facilitate the spontaneous combustion of coal; when the moisture content is higher than a certain value, increasing the moisture content of coal can inhibit the release of CO and hinder the spontaneous combustion of coal; coal with a moisture content of about 14% is the most prone to spontaneous combustion. In addition, moisture content had a dual effect on the development of coal pores. With the increase of moisture content, the pores and cracks of coal increased, but when the moisture content reached a certain level, the pores and cracks of coal were filled with water, suppressing the expansion and generation of coal cracks.